HacA Governs Virulence Traits and Adaptive Stress Responses in Trichophyton rubrum - Bitencourt, Tamires A.; Lang, Elza A. S.; Sanches, Pablo R.; Peres, Nalu T. A.; Oliveira, Vanderci M.; Fachin, Ana Lúcia; Rossi, Antonio; Martinez-Rossi, Nilce M. (Frontiers in Microbiology, 2020)
The ability of fungi to sense environmental stressors and appropriately respond is linked to secretory system functions. The dermatophyte infection process depends on an orchestrated signaling regulation that triggers the transcription of genes responsible for adherence and penetration of the pathogen into host-tissue. A high secretion system is activated to support the host-pathogen interaction and assures maintenance of the dermatophyte infection. The gateway of secretion machinery is the endoplasmic reticulum (ER), which is the primary site for protein folding and transport. Current studies have shown that ER stress that affects adaptive responses is primarily regulated by UPR and supports fungal pathogenicity; this has been assessed for yeasts and Aspergillus fumigatus, in regard to how these fungi cope with host environmental stressors. Fungal UPR consists of a transmembrane kinase sensor (Ire1/IreA) and a downstream target Hac1/HacA. The active form of Hac is achieved via non-spliceosomal intron removal promoted by endonuclease activity of Ire1/IreA. Here, we assessed features of HacA and its involvement in virulence and susceptibility in Trichophyton rubrum. Our results showed that exposure to antifungals and ER-stressing agents initiated the activation of HacA from T. rubrum. Interestingly, the activation occurs when a 20 nt fragment is removed from part of the exon-2 and part of intron-2, which in turn promotes the arisen of the DNA binding site motif and a dimer interface domain. Further, we found changes in the cell wall and cellular membrane composition in the ΔhacA mutant as well as an increase in susceptibility toward azole and cell wall disturbing agents. Moreover, the ΔhacA mutant presented significant defects in important virulence traits like thermotolerance and growth on keratin substrates. For instance, the development of the ΔhacA mutant was impaired in co-culture with keratinocytes or human nail fragments. Changes in the pro-inflammatory cytokine release were verified for the ΔhacA mutant during the co-culture assay, which might be related to differences in pathogen-associated molecular patterns (PAMPs) in the cell wall. Together, these results suggested that HacA is an integral part of T. rubrum physiology and virulence, implying that it is an important molecular target for antidermatophytic therapy.